PENGARUH TINGKAT PUTUS SEKOLAH, KEMISKINAN DAN PENGANGGURAN TERHADAP KRIMINALITAS DI INDONESIA - Maulidya Rahmi; Melti Roza Adry (Universitas Negeri Padang, 2018)
This research aims to know and analyze determine drop out, poverty, and unemployment to criminality in Indonesia. This research use panel least square and Fixed effect model. The estimation result should that elementary school drop out has a positive and significant effect on criminality in Indonesia, poverty doesn’t h ave effect to criminality in Indonesia, unemployment doesn’t have effect to criminality in Indonesia. From the result of this research, goverment and the police should be do some sosialization at school and also give sosialization in front of citizen. The sosialization is about the law of criminality and increasing parents educations and anticipate negativity on environment.